Subclinical elevations of TSH and assisted reproductive technology outcomes - Michalakis, Konstantinos G. (2011)
The prevalence of moderately elevated TSH levels consistent with subclinical hypothyroidism (2.5–4.0 μIU/mL) was 23% in a cohort of 1231 women pursuing assisted reproductive technologies. Preconception elevated levels of TSH were associated with diminished ovarian reserve, but were not associated with adverse ART or pregnancy outcomes.